Impact of a High Coverage Vaccination Rate on Human Papillomavirus Infection Prevalence in Young Women: A Cross-sectional Study. Issue 4 (October 2020) - Saldanha, Conceição; Vieira-Baptista, Pedro; Costa, Mariana; Silva, Ana Rita; Picão, Miguel; Sousa, Carlos
Abstract : Objective: The aim of the study was to compare the rate of high-risk human papillomavirus (HR-HPV) genotypes in vaccinated (Gardasil [quadrivalent]) and unvaccinated cohorts of young women. Materials and Methods: This is a retrospective, cross-sectional study, consisting of the comparison of the prevalence of HPV 16, 18, and other HR genotypes in 2183 women younger than 25 years, according to their birth year (born >1994 [mostly vaccinated <13 years]; born 1992–1994 [vaccinated at 17 years]; born <1992 [not vaccinated/vaccinated >17 years]), in a private laboratory. Results: The rates of HPV 16, 18, 16/18, and others in the cohort born before 1992 (n = 331) were 6.3%, 1.5%, 7.9%, and 31.7%. In those born 1992–1994 (n = 901), the rates were 3.3%, 0.4%, 3.6%, and 32.5%; in the ones born after 1994 (n = 951), the rates were 0.7%, 0.2%, 0.9%, and 33.2%, respectively. There were no changes in the relative risk (RR) of HR-HPV infection by genotypes other than HPV 16/18 in any cohort. The RR was significantly reduced in the cohort born after 1994 for HPV 16 (0.12 [0.050–0.270], p < .0001), HPV 18 (0.14 [0.027–0.714], p = .02), and HPV 16/18 (0.12 [0.057–0.254], p < .0001). In those born 1992–1994, there was a nearly significant reduction in the RR of HPV 18 infection (0.29 [0.079–1.09], p = .07); the reduction was significant for HPV 16 (0.52 [0.305–0.904], p = .02) and HPV 16/18 (0.45 [0.274–0.747], p = .0018). Conclusions: Young women vaccinated before 13 years had a nearly 90% risk reduction of HPV 16/18, whereas if vaccinated at 17 years, the decrease was of 50%. There was no impact in the nonvaccine genotypes. Our data highlight the importance of vaccinating at young age and of introducing vaccines covering more HR genotypes.